2015
DOI: 10.1126/sciadv.1500105
|View full text |Cite
|
Sign up to set email alerts
|

Rapid eye movement sleep promotes cortical plasticity in the developing brain

Abstract: Rapid eye movement sleep plays a critical role in shaping developing circuits in the cerebral cortex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
69
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 134 publications
(75 citation statements)
references
References 28 publications
6
69
0
Order By: Relevance
“…One of the most widely supported ideas in sleep science is that REM sleep functions to facilitate the formation and consolidation of certain types of memory [10,7072], although this notion is not universally upheld [21,42,73,74]. Numerous studies in rodents and humans have shown, for example, that REM sleep deprivation impairs formation (or expression) of spatial and emotional memories.…”
Section: Rem Sleep Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the most widely supported ideas in sleep science is that REM sleep functions to facilitate the formation and consolidation of certain types of memory [10,7072], although this notion is not universally upheld [21,42,73,74]. Numerous studies in rodents and humans have shown, for example, that REM sleep deprivation impairs formation (or expression) of spatial and emotional memories.…”
Section: Rem Sleep Functionmentioning
confidence: 99%
“…Several additional functions have also been ascribed to REM sleep, ranging from facilitating cortical plasticity [10,78] to restoration of aminergic cell/receptor function [79] and heightening general creativity [80,81]. It is worth noting that all of these proposals assume that REM sleep functions to restore some deficit incurred during prior wakefulness.…”
Section: Rem Sleep Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…MD led to a shift in ocular dominance due to a small decline in the visual cortical responses to the deprived eye, and an increase in the response to the non-deprived eye [36,37]. Notably, this shift was promoted by post-MD sleep, probably both NREM sleep [36] and REM sleep [38], but not by sleep deprivation. Two underlying mechanisms have been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…The first few hours of sleep are also characterized by the activation of protein kinases and the synthesis of proteins known to mediate LTP. 89, 90, 92 …”
Section: Proposed Sleep Functionsmentioning
confidence: 99%